PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES SISWA KELAS II B - Trimantara, Hermansyah; ., Miramto; S, Nuryanto A (ATTA`DIB, 2015)
This research aims to improve student learning outcomes class II B SDN 7 Metro North using cooperative learning model examples of non examples. The method used is classroom action research assessment process forms a cycle cycle consisting of four basic stages are interrelated and continuous, namely 1) planning, 2) acting, 3) observing, and 4) reflecting. In this study, researchers used quantitative data analysis techniques such as achievement test and qualitative data analysis techniques such as observation. Based on the results of the data analysis of thematic learning class II B SDN 7 Metro North, affective value of students from the first cycle to the second cycle increased by 19.05% from the first cycle of 62.20% to 81.25% for the second cycle. Value psychomotor students increased an average value of 24.33 from the first cycle of 58.71 into 83.04 in the second cycle. And the students’ cognitive value also increased by 11.79 from the first cycle of 65.54 to 77.32 in the second cycle. From the results of this study indicate that the use of cooperative learning model examples of non examples can improve student learning outcomes.